2021
DOI: 10.1177/03331024211048507
|View full text |Cite
|
Sign up to set email alerts
|

Lasmiditan efficacy in the acute treatment of migraine was independent of prior response to triptans: Findings from the CENTURION study

Abstract: Background A significant proportion of triptan users exhibit an insufficient response or inadequate tolerability to a triptan, and some may develop a contraindication. Lasmiditan, a selective 5-HT1F receptor agonist, may be an option for these individuals. We assessed lasmiditan efficacy in a subgroup of patients in CENTURION (Phase 3 migraine consistency study) who exhibited an insufficient response to triptans, including a subgroup with insufficient response due to efficacy only. Methods Patients were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 34 publications
1
6
0
1
Order By: Relevance
“…Rimegepant has also consistently demonstrated favorable safety and tolerability, which may benefit patients whose insufficient response is due to AEs. The efficacy findings from this analysis are comparable to those seen in the individual rimegepant trials and consistent with the results of post-hoc analyses of the effects of prior triptan exposure on the efficacy of ubrogepant, lasimiditan, and triptans (30,32,35,36). This analysis differs from previous work by distinguishing between participants who had a history of insufficient response to 1 triptan and participants who had a history of insufficient response to 2 triptans.…”
Section: Discussionsupporting
confidence: 81%
“…Rimegepant has also consistently demonstrated favorable safety and tolerability, which may benefit patients whose insufficient response is due to AEs. The efficacy findings from this analysis are comparable to those seen in the individual rimegepant trials and consistent with the results of post-hoc analyses of the effects of prior triptan exposure on the efficacy of ubrogepant, lasimiditan, and triptans (30,32,35,36). This analysis differs from previous work by distinguishing between participants who had a history of insufficient response to 1 triptan and participants who had a history of insufficient response to 2 triptans.…”
Section: Discussionsupporting
confidence: 81%
“…Nonetheless, it remains to be seen whether central inhibition of the trigeminovascular system is required for its efficacy. As the mechanism of action is at least partly different from triptans, lasmiditan may be effective in patients with inadequate triptan response (32,33). In a post-hoc subgroup analysis of a phase 3 study of lasmiditan, 43% of included patients were defined as insufficient responders to triptans based on self-reports (overall response to treatment was rated as good, poor, or none).…”
Section: Response To Lasmiditan Rimegepant and Ubrogepant In Triptan ...mentioning
confidence: 99%
“…These variabilities could be derived from the small number of patients in the 50 mg groups. Previously reported results with a higher sample size demonstrated that efficacy of lasmiditan was independent of history of migraine with aura and prior response to triptans [ 11 , 12 , 31 ]. In summary, although treatment-by-subgroup interactions (by each arm) were observed with respect to the 50 mg dose as a result of the small sample size, our findings suggested that the efficacy of lasmiditan in Japanese patients with migraine is not influenced by migraine disease characteristics.…”
Section: Discussionmentioning
confidence: 99%